PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DI KELAS V SDN 18 KAMPUNG DURIAN KOTA PADANG - Talitha Septia; Elfia Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Introduction of the principle of politeness in language from an early age is a strategic step in the process of forming children's character. Based on findings in the field, there are still many children who do not use language politely. The purpose of this study was to determine the effectiveness of the use of Interactive CD media on children's oral politeness in Pembina Pasaman State Kindergarten. This interactive CD consists of six maxims, namely the Tact Maxim, Generosity, Approbation, Modesty, Agreement, and Sympathy (Leech: 1993). This study used a quasi-experimental method in the form of nonequivalent control group design. The subjects of this study were groups B3 and B4 of Pembina Pasaman State Kindergarten, while the object of the study was the effectiveness of Interactive CD Media on Children's Oral Politeness. The data collection technique used tests and documentation in the form of 10 questions and the data analysis technique used normality tests, homogeneity tests, hypothesis tests, and effect size tests. The data collection tool used a statement sheet. Then the data was processed with a difference test (t-test) using the SPSS 26 application. Furthermore, to determine how effective the Interactive CD media was, the effect size calculation was carried out using the Cohens formula. The results of the study showed a significance value of Levene's Test of 0,444 > 0,05 and sig (2-tailed) of 0,00 < 0,05, which showed a significant difference between the two groups. The conclusion of this study obtained a value of d = 1,69, so that the effectiveness of the Interactive CD media was categorized as high.